A Model of the Entrepreneurial Economy - Audretsch, David; Thurik, Roy (Senate Hall, 2004)
The present paper deals with the distinction between the models of the managed and entrepreneurial economies. It explains why the model of the entrepreneurial economy may be a better frame of reference than the model of the managed economy in the contemporary, developed economies. This is done by contrasting the most fundamental elements of the managed economy model with those of the entrepreneurial economy model. Building upon Audretsch and Thurik (2000 and 2001), Audretsch, Thurik, Verheul and Wennekers (2002) and Thurik and Verheul (2003), fourteen dimensions are identified as the basis for comparing models of the entrepreneurial and the managed economy.
Keywords: entrepreneurship|innovation|knowledge economy and globalization